Window Design of Naturally Ventilated Offices in the Mediterranean Climate in Terms of CO2 and Thermal Comfort Performance - Abdullah, Hardi K.; Alibaba, Halil Z. (Mdpi, 2020)
Natural ventilation through window openings is an inexpensive and effective solution to bring fresh air into internal spaces and improve indoor environmental conditions. This study attempts to address the indoor air quality-thermal comfort dilemma of naturally ventilated office buildings in the Mediterranean climate through the effective use of early window design. An experimental method of computational modelling and simulation was applied. The assessments of indoor carbon dioxide (CO2) concentration and adaptive thermal comfort were performed using the British/European standard BS EN 15251:2007. The results indicate that when windows were opened, the first-floor zones were subjected to the highest CO2 levels, especially the north-facing window in the winter and the south-facing window in the summer. For a fully glazed wall, a 10% window opening could provide all the office hours inside category I of CO2 concentration. Such an achievement requires full and quarter window openings in the cases of 10% and 25% window-to-floor ratios (WFR), respectively. The findings of the European adaptive comfort showed that less than 50% of office hours appeared in category III with cross-ventilation. The concluding remarks and recommendations are presented.
Keywords: window design; natural ventilation; indoor air quality; carbon dioxide (CO2) concentration; thermal comfort; adaptive comfort model; office building; the Mediterranean climate